Semiclassical Estimates of Pressure-induced Line Widths for Infrared Absorption in Hot (Exo)planetary Atmospheres - Jeanna Buldyreva; Kathleen Stehlin; Sergei N. Yurchenko; Elizabeth R. Guest; Jonathan Tennyson (The Astrophysical Journal Supplement Series)
Because of elevated temperatures and high fluxes of stellar radiation irreproducible in laboratory conditions, molecules and molecular ions found or expected in exoplanetary atmospheres are generally poorly characterized from the viewpoint of their spectroscopic line-shape parameters; in many cases, there are no data at all. Advanced theoretical approaches (classical, semiclassical, and quantum mechanical), without mentioning their high computational cost, are also impracticable due to the lack of potential energy surfaces. To fill this gap of crucially missing line-broadening parameters, we provide estimated values issued from a simple rotationally independent semiclassical expression. Only the index related to the leading long-range interaction term, molecular masses and kinetic diameters, as well as temperature are used as input parameters. A wide range of absorbers and perturbation by He, Ar, H _2 , N _2 , O _2 , CO, NO, CO _2 , H _2 O, CH _4 , and NH _3 as well as self-perturbation are considered. The explicit temperature dependence T ^−0.5 allows calculations to be limited to the single reference temperature of 296 K; for other temperatures a simple scaling can be used. The full set of line-broadening coefficients obtained with various possible values of kinetic diameters is provided by the new Collisional Line-broadening Parameters database, which is specifically designed for this purpose. “Midvalue” (or more recent) kinetic diameters are retained to create one-value line-broadening data required to populate the ExoMol database. A way to generate rotationally dependent line widths is proposed.